Antenatal substance misuse and smoking and newborn hypoxic challenge response. Issue 2 (19th August 2015) - Ali, Kamal; Rossor, Thomas; Bhat, Ravindra; Wolff, Kim; Hannam, Simon; Rafferty, Gerrard F; Peacock, Janet L; Greenough, Anne
Abstract : Objectives: Infants of smoking (S) and substance misusing (SM) mothers have an increased risk of sudden infant death syndrome. The aim of this study was to test the hypothesis that infants of SM or S mothers compared with infants of non-SM, non-smoking mothers (controls) would have a poorer ventilatory response to hypoxia, which was particularly marked in the SM infants. Design: Physiological study. Setting: Tertiary perinatal centre. Patients: 21 SM; 21 S and 19 control infants. Infants were assessed before maternity/neonatal unit discharge. Interventions: Maternal and infant urine samples were tested for cotinine, cannabinoids, opiates, amphetamines, methadone, cocaine and benzodiazepines. Main outcome measures: During quiet sleep, the infants were switched from breathing room air to 15% oxygen and changes in minute volume were assessed. Results: The SM infants had a greater mean increase (p=0.028, p=0.034, respectively) and a greater magnitude of decline (p<0.001, p=0.018, respectively) in minute volume than the S infants and the controls. The rate of decline in minute volume was greater in the SM infants (p=0.008) and the S infants (p=0.011) compared with the controls. Conclusions: Antenatal substance misuse and smoking affect the infant's ventilatory response to a hypoxic challenge.